Salmonella Colonization of Production Hens Fed a Parietal Yeast Fraction with High Levels of Mannan and Beta-Glucan - Price , P.T.; Gaydos, T.; Padgett, J.C.; Gardner, K.; Bailey, C. (International Journal of Poultry Science, 2019)
Background and Objective: Salmonella is a gram-negative rod-shaped pathogen responsible for approximately 1 million foodborne illnesses per year in the U.S. Previous studies with highly concentrated levels of mannans (>20%) in yeast cell wall have shown to reduce Salmonella counts in broiler ceca when added to feed. This study was conducted to understand the effects of concentrated mannans on Salmonella in egg producing hens. Materials and Methods: A total of 24 Hy-Line W36 layers were challenged with Salmonella Typhimurium, 12 birds fed basal diet only (Control) and 12 birds fed the basal diet plus treatment of 500 ppm cell wall. At one-week post challenge, all birds were humanely euthanized and cecal prevalence and enumeration were recorded. Results: Cecal counts on birds challenged with S. Typhimurium showed a final count of 4.71 log10 CFU mL–1, while yeast cell wall sample counts were 3.71 log10 CFU mL–1 (p = 0.015). Conclusion: A 1 log reduction of cecal Salmonella is a biologically important result indicating there may be some potential for this yeast cell wall to impact levels of Salmonella Typhimurium in the ceca.